Auditing Procedures (Book). - Claire, Richrd S.; Cannon, Arthur M. (The Accounting Review, 1954)
Reviews the book "Auditing Procedures–An Introduction for the Student-in-Accounts," by H.C. Dell and J.R.M. Wilson.